2020
DOI: 10.1101/2020.05.12.20099945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS pandemic exposure impaired early childhood development: A lesson for COVID-19

Abstract: Social and mental stressors associated with the COVID-19 pandemic may promote long-term effects on child development. However, reports aimed at identifying the relationship between pandemics and child health are limited. We conducted a retrospective study to evaluate the severe acute respiratory syndrome (SARS) pandemic in 2003 and its relationship to child development indicators using a representative sample across China. Our study involved longitudinal measurements of 14,647 children, 36% of whom (n = 5216) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…These findings are comparable to studies on the psychological impact of previous emergencies and disasters (e.g. epidemics, terrorist attacks, hurricanes, floods) ( Danese et al, 2020 ; Fan et al, 2020 ; Sprang and Silman, 2013 ). Young people may mostly experience transient symptoms such as fear, detachment, numbness and feelings of worry that an event will reoccur ( Danese et al, 2020 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These findings are comparable to studies on the psychological impact of previous emergencies and disasters (e.g. epidemics, terrorist attacks, hurricanes, floods) ( Danese et al, 2020 ; Fan et al, 2020 ; Sprang and Silman, 2013 ). Young people may mostly experience transient symptoms such as fear, detachment, numbness and feelings of worry that an event will reoccur ( Danese et al, 2020 ).…”
Section: Discussionsupporting
confidence: 84%
“…People are forced to work from home and nurseries, schools, universities are closed. Many sports and social events have been cancelled ( Fan et al, 2020 ; Fegert et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective analysis of the 2003 SARS pandemic showed that children had delayed childhood development, including gross motor and language development. 21 Given our study design, it is impossible to confirm and quantify the extent of the regression in our children’s developmental milestones. Further research needs to be designed to confirm these findings.…”
Section: Discussionmentioning
confidence: 96%